Digital Marketing Strategy Based on Social Media and Word of Mouth in Enhancing Brand Awareness and Consumer Purchase Decisions - I Nyoman Tri Sutaguna; Adi Artino; Angga Kurniawan; Ansri Jayanti; Riesna Apramilda (SAJMR : Southeast Asian Journal of Management and Research, 2026)
This study aims to analyze the role of digital marketing strategies based on social media and word of mouth (WOM) in enhancing brand awareness and consumer purchase decisions. This research employs a Systematic Literature Review (SLR) approach using the PRISMA framework to identify, evaluate, and synthesize relevant studies published between 2019 and 2025. A number of selected articles from Scopus-indexed and reputable journals were analyzed. The findings indicate that social media marketing significantly improves brand awareness through consumer engagement, interaction, and information dissemination. Meanwhile, word of mouth plays a crucial role in building consumer trust and influencing purchase decisions through recommendations and shared experiences. Furthermore, the integration of social media and word of mouth provides a stronger and more sustainable impact on consumer behavior, particularly in shaping brand perception and purchase intention